On a radial positive solution to a nonlocal elliptic equation - Fijalkowski, Piotr; Przeradzki, Bogdan (Topological Methods in Nonlinear Analysis, 2003)
The existence of a solution to the Dirichlet boundary value problem for nonlinear Poisson equations with the nonlocal nonlinear term -Δ u=f(u,(g° u)),uU=0, is proved by means of fixed point theorems for increasing compact operators.